Sustainable Cementitious Materials: Applications and Potentialities of PCR-PET - Brandão, Raul de Souza; Lima, José Augusto Pedro; Alexandre, Jonas (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
This article explores the applicability of Post-Consumer Recycled Polyethylene Terephthalate (PCR-PET) in sustainable cementitious materials, highlighting its relevance to sustainable construction. It discusses the incorporation of recycled PET into a variety of cementitious materials such as mortar, concrete, pavements, blocks, bricks, pipes, artificial rocks, panels, urban furniture, and tiles, demonstrating the environmental and technical benefits of these materials. Additionally, it presents case studies and experimental results illustrating the effective application of PCR-PET in these areas. These studies reveal, in some cases, the positive influence of adding recycled PET on the properties of materials, from mechanical strengt and durability to thermal and acoustic performance of applications. Finally, it emphasizes the role of PCR-PET in reducing plastic waste, promoting circular economy, and contributing to sustainability in the construction industry. In summary, this article underscores the potential use of PCR-PET as an essential tool for advancing sustainable construction, providing innovative and responsible solutions to the environmental challenges faced by the construction materials industry.